Dynamic programming and the calculus of variations - Dreyfus, Stuart E. (New York : London : Academic Press, 1965)
The calculus of variations is a mathematical discipline that treats certain problems in the area of optimization theory. A more recent mathematical formalism, dynamic programming, is also applicable to optimization problems. In this book the relationships between these two techniques are developed.
Includes index
Bibliography: p. 242-244.
ne 03/04/2018
Loans
Keywords: Dynamic programming; Calculus of variations